The Prevalence and Antimicrobial Susceptibility of Bacterial Uropathogens Isolated from Pediatric Patients - R Ranjbar; MT Haghi-Ashtiani; N Jonaidi Jafari; M Abedini (Tehran University of Medical Sciences, 2009)
Background: Urinary tract infection (UTI) is considered as the most common bacterial infectious disease seen among the pediatric patients. The aim of this study was to investigate the prevalence and antimicrobial susceptibility of bacterial uropathogens isolated from the pediatric patients with urinary tract infections. Methods: This descriptive study was conducted in Children Medial Center, Tehran, Iran from March 2006 to Feb 2007. Clean-catch midstream urine specimens were obtained from the patients and cultured on the appropriate bacteriological media. Bacterial isolates were identified by standard biochemical and serological tests. Antimicrobial susceptibility testing was performed according to CLSI guidelines. Results: From 14199 urine specimens, 16.2% had positive results for bacterial cultures. Nine hundred twenty one strains were identified as Escherichia coli; 412 as Klebsiella spp., 285 as Coagulase negative Staphylocococci, 202 as Enterococcus spp., 158 as Pseudomonas spp., and 83 as Staphylococcus aureus. E. coli isolates showed high resistance to carbenicillin (68%), ampicillin (96%), trimethoprim-sulfomethoxazol (70%) and kanamycin (65%). More than 30% of isolates of Klebsiella spp., Pseudomonas spp. and Enterobacter spp. have shown high degree of resistance to commonly used antibiotics. Conclusion: Our findings reinforce the need for ongoing investigation to show trends in antibiotic resistance, which can help to prescribing of antibiotics in clinics.